Pulsing with low concentration gibberellin plus benzyladenine or commercial floral preservatives affect postharvest longevity, quality, and leaf chlorosis of cut lilies and gladioli - Ahmad, Iftikhar; Dole, John M.; Favero, Bruno T. [UNESP] (American Society for Horticultural Science, 2014)
Effects of pulsing with different concentrations of gibberellin plus benzyladenine (GA4+7 + BA), a proprietary mixture of GA4+7 plus BA in a commercial floral preservative (GA4+7 + BA + preservative), or a propriety mixture of sugar plus acidifier developed for bulbous flowers (floral bulb preservative) were studied on postharvest performance and quality of cut lily (Lilium hybrids) and gladiolus (Gladiolus hybrids) flowers. Pulsing of cut stems of lily with GA4+7 + BA at 5 or 2 mL•L−1 GA4+7 + BA + preservative for 20 hours at 3 ± 1 °C extended the vase life and controlled leaf chlorosis of ‘Cobra’ oriental lily and ‘Cappuccino’ and ‘Dot Com’ asiatic lily. Cut ‘Orange Art’ asiatic lily performed best when pulsed with GA4+7 + BA at 10 mg•L−1. For cut gladiolus, pulsing with GA4+7 + BA at 10 mg•L−1 extended the vase life of ‘Alice’, ‘Mammoth’, and ‘Passion’, while ‘Scarlet’ had the longest vase life when pulsed with 5 mg•L−1 GA4+7 + BA. GA4+7 + BA + preservative also extended the vase life and controlled leaf chlorosis, but the floral bulb preservative had no effect on vase life extension or preventing leaf chlorosis of lilies. Gladiolus cultivars had no or minor leaf chlorosis during vase period. Overall, overnight pulsing with GA4+7 + BA or GA4+7 + BA + preservative extended the vase life and prevented leaf chlorosis and can be used by growers and wholesalers for maintaining quality of cut stems.
Keywords: Plant growth regulators; Senescence; Vase life